Influence of solution annealing temperature and cooling medium on microstructure, hardness and corrosion resistance of martensitic stainless steel X46Cr13. Issue 10 (29th January 2015) - Rosemann, P.; Kauss, N.; Müller, C.; Halle, T.
<x xml:space="preserve">Abstract</x> The corrosion behavior of carbon containing martensitic stainless steels depends strongly on the applied heat treatment which determines the distribution of carbon and chromium in the microstructure. This work's focus is on the effect of solution annealing on microstructure, hardness and the resulting corrosion resistance of the martensitic stainless steel X46Cr13. Solution annealing was performed at selected temperatures based on thermodynamic calculations of the chromium and carbon contents in solid solution and the chemical composition of the remaining carbides as function of temperature. The corrosion resistance was investigated with electrochemical potentiodynamic reactivation (EPR) and the KorroPad (KP) technique. The results indicate a large influence of the solution treatment temperature, duration and cooling rate on passivation behavior and pitting corrosion resistance. Higher solution annealing temperatures increase the amount of chromium and carbon dissolved in solid solution resulting in easier passivation and higher hardness. If diffusion is enabled by slow air‐cooling, chromium depletion was detected causing high susceptibility to pitting corrosion.